Flexible cellulose-based piezoelectric composite membrane involving PVDF and BaTiO3 synthesized with the assistance of TEMPO-oxidized cellulose nanofibrils. Issue 15 (31st March 2023) - Li, Meilin; Jiang, Bei; Cao, Shuoang; Song, Xinyi; Zhang, Yuanqiao; Huang, Lijun; Yuan, Quanping
Abstract : Cellulose nanofibrils (CNF) with abundant oxygen-containing groups acts as even and nanoscale nucleation sites for the synthesis of BaTiO3 which was incorporated in CNF and PVDF to fabricate flexible composite piezoelectric membrane. Abstract : High-performance flexible barium titanate (BaTiO3 )-based piezoelectric devices have gained much attention. However, it is still a challenge to prepare flexible polymer/BaTiO3 -based composite materials with uniform distribution and high performance due to the high viscosity of polymers. In this study, novel hybrid BaTiO3 particles were synthesized with assistance of TEMPO-oxidized cellulose nanofibrils (CNFs) via a low-temperature hydrothermal method and explored for their application in piezoelectric composites. Specifically, Ba 2+ was adsorbed on uniformly dispersed CNFs with a large amount of negative charge on their surface, which nucleated, resulting in the synthesis of evenly dispersed CNF-BaTiO3 . The obtained CNF-BaTiO3 possessed a uniform particle size, few impurities, high crystallinity and dispersity, high compatibility with the polymer substrate and surface activity due to the existence of CNFs. Subsequently, both polyvinylidene fluoride (PVDF) and TEMPO-oxidized CNFs were employed as piezoelectric substrates for the fabrication of a CNF/PVDF/CNF-BaTiO3 composite membrane with a compact structure, displaying the tensile strength of 18.61 ± 3.75 MPa and elongation at break of 3.06 ± 1.33%. Finally, a thin piezoelectric generator (PEG) was assembled, which output a considerable open-circuit voltage (4.4 V) and short-circuit current (200 nA), and could also power a light-emitting diode and charge a 1 μF capacitor to 3.66 V in 500 s. Its longitudinal piezoelectric constant ( d 33 ) was 5.25 ± 1.04 pC N −1 even with a small thickness. It also exhibited high sensitivity to human movement, outputting a voltage of about 9 V and current of 739 nA for only a footstep. Thus, it exhibited good sensing property and energy harvesting property, presenting practical application prospects. This work provides a new idea for the preparation of hybrid BaTiO3 and cellulose-based piezoelectric composite materials.